Analysis of earth‐to‐satellite free‐space optical link performance in the presence of turbulence, beam‐wander induced pointing error and weather conditions for different intensity modulation schemes. Issue 18 (1st December 2015) - Viswanath, Anjitha; Jain, Virander Kumar; Kar, Subrat
Abstract : In this study, the authors evaluate the performance of an earth‐to‐satellite free‐space optical link in terms of bit error rate (BER) for three intensity modulation (IM) schemes [on–off keying (OOK), M ‐ary pulse position modulation ( M ‐PPM) and M ‐ary differential PPM ( M ‐DPPM)] and direct detection receiver. The performance is analysed in the presence of atmospheric turbulence, beam‐wander induced pointing error and weather conditions. Turbulence with beam wander effect is modelled using gamma‐gamma distribution and the weather effects are incorporated using the Beer‐Lambert law. They obtain closed form BER expressions for the above IM schemes using combined channel state probability density functions. They show that for the same average power, M ‐PPM offers the best performance, followed by M ‐DPPM and OOK schemes. Link performance degrades for all IM schemes with increase in the value of ground level refractive index structure parameter and bit rate. Presence of weather conditions like moderate, light and thin fog increase signal attenuation and this increase may be very high in case of thick and dense fog or clouds and can lead to link failure.